2007
DOI: 10.1111/j.1468-3148.2007.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

What Factors are Related to a Negative Outcome of Self‐Injurious Behaviour During Childhood in Pervasive Developmental Disorders?

Abstract: Aim To explore the factors related to the outcome of self-injurious behaviour (SIB) in children with pervasive developmental disorders (PDD). Method Children with PDD were assessed on individual and environmental variables at time 1 and 3 years later. A questionnaire about the presence or absence of SIB was also administered at both times in order to examine the early course of SIB. Results Our findings suggest an association between a negative outcome and several aspects of the children's behaviour. Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 23 publications
10
46
1
2
Order By: Relevance
“…The relative risk of a child with ASD engaging in SIB at 24 months was almost two-fold that of a child without a diagnosis. These data are consistent with previous work and suggest that SIB emerges early in life, can be persistent, and is prevalent among children with ASD (e.g., Baghdadli et al 2008; Berkson et al 2001; Schroeder et al 2014). Almost half of the participants who engaged in SIB at Time 1 persisted in engaging in SIB at follow up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The relative risk of a child with ASD engaging in SIB at 24 months was almost two-fold that of a child without a diagnosis. These data are consistent with previous work and suggest that SIB emerges early in life, can be persistent, and is prevalent among children with ASD (e.g., Baghdadli et al 2008; Berkson et al 2001; Schroeder et al 2014). Almost half of the participants who engaged in SIB at Time 1 persisted in engaging in SIB at follow up.…”
Section: Discussionsupporting
confidence: 91%
“…Almost half of the participants who engaged in SIB at Time 1 persisted in engaging in SIB at follow up. Other studies report high persistence estimates among individuals with intellectual disabilities (Taylor et al 2011) and children with PDD-NOS (Baghdadli et al 2008). Based on these data, it is likely that once proto-injurious behavior or SIB emerges, it may remain stable, and should be evaluated even if it is not yet severe yet.…”
Section: Discussionmentioning
confidence: 94%
“…Twenty‐three per cent of the young children in Berkson et al . 's (2001) study showed transient SIB without chronic topographies, Baghdadli et al . (2008) found that only 52% of children with ASDs aged 2–7 showing SIB continued to do so 3 years later, and Chadwick et al .…”
Section: Resultsmentioning
confidence: 97%
“…The high prevalence of SIB in ASD has led to research investigating risk factors to better define this relationship. Some studies have shown that children with ASD have a higher risk of SIB if they have a younger chronological age or the presence of an associated perinatal condition (Baghdadli et al 2003), early speech deficits (Baghdadli et al 2008), limited daily living skills, or greater severity of ASD symptoms (Baghdadli et al 2003(Baghdadli et al , 2008. Other research has found stereotypy (Richman et al 2013), atypical sensory processing (Duerden et al 2012), and impulsivity to be predictors of SIB in individuals with ASD (Duerden et al 2012;Richman et al 2013).…”
Section: Phenomenology Of Sibmentioning
confidence: 93%